Association between wasting and inadequate breastfeeding practices among infants under six months in SNNPR and Somali regions of Ethiopia: A multilevel cross-sectional study. - Bethel Getachew; Yemane Berhane; Yadeta Dessie; Walelegn W Yallew; Hanna Y Berhane; Sunny S Kim (PLoS ONE)
Background Wasting is a severe threat to children's survival and development. Attaining optimal breastfeeding practices for infants under six months of age remains a significant challenge in low-income countries. This study assessed the association between wasting and breastfeeding practices among infants under six months of age in the SNNPR and Somali regions of Ethiopia. Methods The study used data from a large feasibility study conducted in the SNNPR and Somali regions of Ethiopia, from August-September 2021. This study involved 895 infants under six months of age with their mothers. The Poisson regression model with robust variance estimation was used to produce adjusted prevalence ratios (APRs) with 95% confidence intervals (CIs). Results The prevalence of wasting was 16.5% (95% CI: 14.2, 19.2) among infants under six months of age. Non-exclusive breastfeeding (APR = 1.50; 95% CI:1.02, 2.21), delayed initiation of breastfeeding (APR = 1.52; CI:1.00, 2.30), being male infants (APR = 1.50; 95% CI:1.09, 2.07), and mothers who attained primary level (APR = 0.62; 95% CI: 0.40, 0.95) or secondary level education (APR = 0.30; 95% CI: 0.09, 0.99) were independently associated with wasting in the multivariable analysis. Conclusion This study indicates a high prevalence of wasting among infants under six months of age. Non-exclusive breastfeeding and delayed initiation of breastfeeding were the modifiable factors significantly linked to infant wasting. Strengthening breastfeeding promotion and support may help reduce wasting in infants under six months.